Acceptance of Elective Single-embryo Transfer in a Resource-limited Setting: A Cross-sectional Questionnaire-based Study - Nithya Panapakkam Jayakumar; Megha Solanki; Reka Karuppusami; Treasa Joseph; Thayparmbil Kunjummen Aleyamma; Mohan Shashikant Kamath (Journal of Human Reproductive Sciences)
Background: While elective single-embryo transfer (eSET) has been advocated in select countries, the global acceptance of the eSET policy has been undermined due to various issues. It is imperative to understand the couples’ perspectives regarding the number of embryos transferred. Aims: We planned a study to evaluate the knowledge and attitude of infertile couples undergoing assisted reproductive technology towards eSET in self-funded treatment cycles in a low-resource setting. Settings and Design: We conducted a cross-sectional study at a tertiary-level referral facility between February 2020 and September 2022. Materials and Methods: This was an interviewer-administered questionnaire-based survey in two stages. The first stage involved the assessment of the knowledge of the participants. Following this, participants were given an information pamphlet and the second stage of the interview was conducted to assess the attitude and change in preference for embryo transfer number. Statistical Analysis Used: The Chi-square and Fisher’s exact test were applied to find an association between categorical variables. Logistic regression was used to assess the association between factors and outcomes. Results: eSET was the preferred choice for only 5.8% of the participants. Following our educational intervention using an information leaflet, there was a statistically significant increase in the preference for eSET (P = 0.01). Univariate logistic regression analysis revealed that participants with a monthly income of ≤50,000 INR had a significantly higher preference for eSET. Conclusion: Continued emphasis on the risks of double-embryo transfer coupled with individualised selection criteria for eSET may help to achieve reasonable congruency between the clinician and couples’ decision.